American swastika inside the white power movement's hidden spaces of hate - Simi, Pete.; Futrell, Robert; ebrary, Inc. (Lanham, Md. : Rowman & Littlefield Publishers, 2010)
"American Swastika takes readers through hidden enclaves of hate in America, exploring how White Supremacy movements thrive nationwide, even as the country on the surface advocates racial equality. The authors explain the difference between movements such as the KKK, the Aryan Nation, and Skinheads, among others, then discuss the various ways White Supremacists cultivate, maintain, and spread their beliefs, largely under the radar of most Americans." "Authors Pete Simi and Robert Futrell draw on over a decade of research and interviews, from the infamous Hayden Lake Aryan compound in Northern Idaho, to private homes in L.A., to hate music concerts around the country. Through descriptive case studies, the authors look at hate in the home, talking with parents who aim to raise "little Hitler" and discussing the impact home schooling and cultural isolation can have on children. The authors also describe Aryan crash pads, Bible studies, and rituals, take readers through the hate music scene from underground bars to massive rallies, and examine how the Internet has shaped communication and created disturbing new virtual communities."--BOOK JACKET.
Hidden spaces of Aryan hate -- Contemporary Aryan hate -- Aryan hate in the home -- Hate parties -- The white power music scene -- Virtual hate -- Private Aryan communities -- Enduring white power activism : estimating the Aryan threat and what to do about it -- Appendix. Making contact and developing rapport.
Includes bibliographical references (p. 133-161).
Electronic reproduction.
Keywords: White supremacy movements -- United States; Hate groups -- United States; Racism -- United States; Terrorism -- United States; United States -- Race relations; Electronic books